Drug-Molecule Adsorption onto Silicon-Doped Fullerene: A Density Functional Theory Study - Yosephine Novita Apriati; Bambang Kristiawan; Nikmatul Jannah; Ari Dwi Nugraheni; Sholihun Sholihun (Indonesian Journal of Chemistry, 2023)
Density functional theory calculations were performed to study the interactions between the host material Si-doped fullerene and the drug molecules paracetamol, a pain and fever reducer, and hydroxyurea, a drug for leukemic treatment. All atoms were relaxed so that the atomic force was less than 5.0 × 10−3 eV/Å. Structural and electronic properties, such as adsorption energy, formation energy, and charge transfer, were calculated. Results showed that Si-doped fullerene had more negative adsorption energy and lower formation energy than undoped fullerene, indicating that drug molecules could be chemisorbed in Si-doped fullerene. These results contribute to the future drug delivery application.